An evaluation of the levels of vitamin D and bone turnover markers after the summer and winter periods in Polish professional soccer players - Kopec, A.; Solarz, K.; Majda, F.; Slowinska-Lisowska, M.; Medras, M. (Journal of Human Kinetics, 2013)
Vitamin D is synthesised in the skin during exposure to sunlight. The fundamental roles of vitamin D are the regulation of calcium and phosphate metabolism and bone mineralisation. Low vitamin D levels in athletes may adversely affect their exercise capabilities. The aim of our study was to investigate changes in serum levels of 25(OH)D3, calcium and bone turnover markers in football players in two training periods differing in the exposure to sunlight (after the summer period and after the winter period). We investigated 24 Polish professional soccer players. Serum levels of the following parameters were determined: 25(OH)D3, calcium, osteocalcin (OC), parathormone (PTH), procollagen type I N - terminal peptide (P1NP), and beta - CrossLaps (beta - CTx). We showed significantly higher levels of 25(OH)D3 and calcium and lower levels of PTH after the summer period versus the winter period. No significant differences in the levels of bone turnover markers were found. Furthermore, we did not observe any significant correlations between the levels of 25(OH)D3 and other parameters. Normal levels of 25(OH)D3 were observed in 50% of the players after the summer period and only in 16.7% of the players after the winter period. It is justified to measure the levels of 25(OH)D3, calcium and PTH in soccer players, especially after the winter period, when the exposure to sunlight is limited.